Coccidioidal Peritonitis: A Review of 17 Cases. (19th January 2022) - Johnson, Royce H; Sharma, Ritika; Sharma, Rupam; Civelli, Valerie; Narang, Vishal; Kuran, Rasha; Goldstein, Ellie J C; Deresinski, Stan; Jones, Amber; Ramzan, Amin; Posalski, Irving; El-sayed, Dena; et al.
Abstract: Coccidioidomycosis is the second most common endemic fungal infection in the United States. Prior descriptions of coccidioidal peritonitis include only single cases. We describe 17 new cases previously unreported from healthcare institutions in California. The majority of cases presented with nonspecific abdominal complaints. PubMed and Google Scholar were searched for additional case series and only single case reports and reviews of single cases were found. The diagnosis was confirmed by culture or histopathology and/or serology in each patient. All patients were treated with anti-fungal therapy. This case series demonstrates that coccidioidal peritonitis may be asymptomatic or present with only subtle abdominal symptoms. In a minority of our patients, the diagnosis was established incidentally during surgery. Based on this series, the overall outcome of coccidioidal peritonitis is favorable with long-term triazole treatment. The term cure is not usually used in disseminated coccidioidal disease because of the risk of late relapse. Abstract : In the United States, coccidioidomycosisis second most common endemic fungus. Descriptions of cocci peritonitis include single cases and reviews. We identified 17 cases of coccidioidal peritonitis throughout California. Coccidioidal peritonitis presents incidentally or with subtle abdominal symptoms.